PERANCANGAN ILUSTRASI CANDI BESERTA ARCA-ARCA PRAMBANAN DENGAN GAYA PIXEL ART DAN IMPLEMENTASINYA PADA DESAIN KAOS - Arif Maulana; Fani Annisa Sya'bina; Safana Azka Djalulia; Defi Nurul Amalia; Siska Sugiharti; Agfa Refangga Irawan (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2026)
Prambanan Temple is a valuable cultural heritage, but preservation efforts through merchandise are often hampered by conventional visuals that are unattractive to younger generations. On the other hand, pixel art, a popular form of digital art in pop culture, offers a unique and nostalgic aesthetic, but its potential to represent the beauty of temples has not been widely explored. The objectives of this study are: (1) To design pixel illustrations of Prambanan Temple and its main statues, (2) To implement the designs on T-shirt products. The background of this study is to participate in the preservation of the Prambanan Temple site. This design report uses a qualitative descriptive approach and focuses on the creation of the artwork. The data collection process to meet the research needs used observation and literature study methods. The process of creating artwork went through three stages, namely exploration, design, and production. The results of this research are five T-shirt designs featuring pixel art illustrations of Prambanan Temple, the statues of Shiva, Durga, Ganesha, Brahma, and Vishnu. These designs successfully combine the beauty of complex temples and statues with the bold and minimalist aesthetics of pixel art. Thus, this research not only enriches visual literacy but also offers an alternative model for the development of innovative and high-artistic-value cultural products